Overcoming the evening/weekend effects on time delays and outcomes of endovascular stroke therapy: the Calgary Stroke Program experience - Almekhlafi, Mohammed A; Hockley, Aaron; Desai, Jamsheed A; Nambiar, Vivek; Mishra, Sachin; Volny, Ondrej; Eesa, Muneer; Demchuk, Andrew M; Menon, Bijoy K; Goyal, Mayank (Journal of neurointerventional surgery, 2014)
BACKGROUND: Stentrievers have resulted in faster recanalization times in patients with acute ischemic stroke. Nonetheless, when strokes occur during evenings and weekends, delays are introduced in achieving this goal. We assessed the feasibility of achieving fast and successful endovascular reperfusion in patients with stroke treated during evenings and weekends and whether this has an impact on the outcome. METHODS: A retrospective review was performed of a longitudinal database of patients with acute anterior ischemic stroke treated with endovascular therapy in a comprehensive stroke center between January 2011 and December 2012. The imaging to reperfusion time was defined as the time from completion of the unenhanced CT scan to the time of angiographic successful reperfusion (TICI 2b-3). This time interval was compared between patients treated during working hours (Monday to Friday 07:00-18:00 h) and those treated in the evening outside these hours and at weekends. The 24-h NIH Stroke Scale score and 90-day favorable outcome score (modified Rankin scale ≤2) were compared between the two groups. RESULTS: In a cohort of 110 patients, 56 (50.9%) were treated on evenings and weekends. The median imaging to reperfusion time in these patients was 111 min compared with 90 min during working hours (p=0.019). The proportion of patients with successful reperfusion (TICI 2b or 3) during the evenings and weekends was 82.1% compared with 76.7% during working hours (p=0.4). The proportion of patients with a 90-day favorable outcome was not significantly different in the two groups (64.3% in those treated during evenings and weekends vs 52.1% in working hours, p=0.2). CONCLUSIONS: Some delays were encountered during evenings and weekend hours. Despite that, it was feasible to achieve a relatively short imaging to reperfusion times during these hours, in comparison to existing literature. A target universal time metric is needed to assess the timeliness of endovascular therapy in stroke centers.
Keywords: ženské pohlaví; lidé; senioři; Stroke; Aged; Time Factors; Humans; výsledek terapie; retrospektivní studie; Tomography, X-Ray Computed; mužské pohlaví; Neuroimaging; endovaskulární výkony; Male; Retrospective Studies; časové faktory; počítačová rentgenová tomografie; Treatment Outcome; neurozobrazování; Endovascular Procedures; cévní mozková příhoda; Female